The impact of the rural environment and environmental conservation on poverty alleviation: the moderating effect of tourism resources - Komathi Wasudawan,; Rossazana Ab-Rahim, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The rural environment adds value to the countryside that provides socio-economic development while environmental conservation draws attention to the locals protecting the environment from deforestation. In line with the Stakeholder Theory, this study examines the impact of the rural environment and environmental conservation on poverty alleviation; tourism resources are used as a moderator to measure the strength of endogenous and exogenous variables. Data was collected from 520 respondents in Kuching and Miri, Sarawak, Malaysia. Partial Least SquareStructural Equation Modelling (PLS-SEM) was used to analyse the hypotheses. The results of the study indicate that tourism contributes to an increase in the household income of locals; however, there is a negative relationship between rural environment, tourism resources and poverty alleviation due to the high cost of private transportation to the rural areas. The results imply that the improvement inaccessibility of public transportation to the rural areas would increase the use of tourism resources and tourist arrivals, and enhance the well-being of local communities. This study also contributes to the literature on rural environment, environmental conservation, tourism resources, poverty alleviation and Stakeholder Theory.